Pham Thu Thuy on Gender and women's participation in REDD+ - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Gender and women's participation in REDD+ national decision-making in Vietnam Presentation by Pham Thu Thuy from CIFOR at the seminar on Closing the gender gap in farming under climate change held 19 March 2015 in Paris. Read more about the event: https://ccafs.cgiar.org/events/closing-gender-gap-farming-under-climate-change-new-knowledge-renewed-action